Paradoxical effects of osteoprotegerin on vascular function: inhibiting inflammation while promoting oxidative stress?. Issue 5 (18th March 2022) - Le, Nhat-Tu; Olmsted-Davis, Elizabeth A.; Abe, Jun-ichi
Abstract: Osteoprotegerin (OPG), also known as osteoclastogenesis inhibitory factor or tumor necrosis factor receptor superfamily member 11B, is well known as a modulator of bone remodeling. The contribution of OPG to cardiovascular disease (CVD) has been suggested, but its molecular mechanism is complex and remains unclear. In the present study, Alves-Lopes et al. ( Clin. Sci. (Lond.) (2021) 135 (20): https://doi.org/10.1042/CS20210643) reported the critical role of syndecan-1 (SDC-1, also known as CD138), a surface protein part of the endothelial glycocalyx, in OPG-induced vascular dysfunction. The authors found that in endothelial cells (ECs), through SDC-1, OPG increased eNOS Thr 495 phosphorylation, thereby inhibiting eNOS activity. Furthermore, the OPG–SDC-1 interaction increased reactive oxygen species (ROS) production through NOX1/4 activation. Both the reduced eNOS activity and induced ROS production inhibited NO production and impaired EC function. In vascular smooth muscle cells (VSMCs), the OPG–SDC-1 interaction increased ROS production through NOX1/4 activation, subsequently increased MLC phosphorylation-mediated Rho kinase-MYPT1 regulation, leading to increased vascular contraction. Ultilizing wire myography and mechanistic studies, the authors nicely provide the evidence that SDC-1 plays a crucial role in OPG-induced vascular dysfunction. As we mentioned above, the molecular mechanism and roles of OPG in cardiovascular system are complex and somewhat confusing. In this commentary, we briefly summarize the OPG-mediated signaling pathways in cardiovascular system.